The Impact of Liver Metastasis on Anti-PD-1 Monoclonal Antibody Monotherapy in Advanced Melanoma: Analysis of Five Clinical Studies - Wang, Xuan; Ji, Qing; Yan, Xieqiao; Lian, Bin; Si, Lu; Chi, Zhihong; Sheng, Xinan; Kong, Yan; Mao, Lili; Bai, Xue; Tang, Bixia; Li, Siming; et al. (Frontiers in Oncology, 2020)
Abstract: Anti-PD-1 monoclonal antibody is becoming a standard treatment for advanced melanoma with durable responses and prolonged survival, but the prognosis is still unsatisfactory for patients with liver metastases. Here, we analysed 5 clinical studies (second-line or above, JS001-I-PK, CT4, KN151, BGB-A317-102, SHR-1210-102, from 2015 to 2018) of anti-PD-1 monotherapy for advanced melanoma to explore prognostic variables of patients with liver metastases. A total of 187 patients were included, among which 47 had liver metastasis and 140 did not. The objective response rate (ORR) of the non-liver metastasis group (18.6%) was significantly higher than that of the liver metastasis group (18.6 vs. 4.3%, p<0.05). The median PFS was 3.6 months with liver metastasis versus 7.4 months with non-liver metastasis (p<0.05). The non-liver metastasis group also had a longer median OS than the liver metastasis group (22.8 vs. 15.7 months, p<0.05). Multivariate analysis showed that liver metastasis was negatively associated with PFS. In the liver metastasis group, it was found that liver metastases compared to other metastases responded worst to anti-PD-1 monotherapy, and were most likely to progress. Intrahepatic progression (defined as an increase in liver metastases by more than 20% from baseline or having new liver metastases, p<0.05) proved to be negatively associated with OS, which indicates the necessity to find a more effective therapy that can target liver metastasis. Interestingly, with a median PFS of 6 months and OS of 30.9 months, previous oncolytic virotherapy might bring more benefits to patients with liver metastasis, but it lacks more accurate analysis because of the low number of samples. These findings emphasize that liver metastasis is a poor prognostic factor for advanced melanoma treated with anti-PD-1 monotherapy. Further exploration is still needed to find a new treatment approach for these patients.